Ai prodromi del Neuhumanismus tedesco: letteratura e pedagogia - Kaiser, Anna (Studi sulla Formazione/Open Journal of Education, 2019)
The relationship of pedagogy with literature emerges as decisive during the Century of Goethe, that of the German Neuhumanismus, which centers on the idea of Bildung. It, like every current of thought and ideas, takes its origin from the visions of the world, from ideals, from the criticalities that, in the previous decades, have been elaborated. In the first half of the eighteenth century, enlightenment and pietism are intertwined, with their pedagogical inspiration that leads to the Germanization of culture; Lessing, Klopstock and Wieland write, bearers of a pedagogical telos station; the German literary revolution begins with the Sturm und Drang, apt to express, albeit chaotically, the anthropological nature in its frankness, even formative